From double-four-ring germanosilicates to new zeolites: in silico investigation - Trachta, Michal; Bludský, Ota; Čejka, Jiří; Morris, Russell E; Nachtigall, Petr (Chemphyschem, 2014)
To date, the majority of zeolites have been prepared by the solvothermal route using organic structure directing agents. Two new zeolites with structural codes PCR and OKO were recently prepared from UTL germanosilicate by removal of the double-four ring (D4R) connecting the dense two-dimensional layers [Nature Chem. 2013, 5, 628]. The corresponding experimental protocol, Assembly-Disassembly-Organization-Reassembly (ADOR), is explored in this contribution with an in silico investigation. The structure and properties of hypothetical zeolites that could be obtained from zeolites with IWW, IWV, IWR, ITR, and ITH topologies using the ADOR protocol are reported based on a computational investigation. A total of 20 new structures are presented together with their characteristics.
Keywords: zeolites; density functional calculations; in silico studies; synthesis; structure